Conservative treatment of scaphoid fracture: Protocol for a systematic review (Research, Society and Development, 2022)
The scaphoid is the most commonly fractured carpal bone. Fractures affecting this bone affect young and active patients between 15 and 40 years of age. Stable scaphoid fractures are treated conservatively by plaster cast immobilization or other type of orthosis for an average period of four to 12 weeks. Failure to treat scaphoid fractures may result in avascular necrosis, nonunion, and early secondary osteoarthritis, which may result in significant economic and social impact due to the affected population, formed by young people of productive age. The management of this type of fracture varies significantly between different Institutions and orthopedic surgeons. This article describes a protocol for a systematic review that aims to evaluate the effects (benefits and harms) of conservative interventions in the treatment of scaphoid fractures in adults.